Artemis and an environmentally sustainable future beyond earth. (December 2022) - Kaufman, Jason A.; Floyd, T. Elliott; Lenartz, Andrew
Highlights: The Artemis program marks the first step in humanity's return to the Moon. The program is reliant upon local environmental resources to support human missions. Resource sustainability is already built into the Artemis program. International policy needs to include language to protect planetary environments. Humanity must be stewards of the planets, not merely consumers of their resources.